The Variation in anthocyanin content level in four local varieties of black rice (Oryza sativa L.) from Indonesia - Basith, Abdul; Noer, Shafa Noer; Faizah, Mazidatul (Jurnal Pertanian, 2023)
Anthocyanin is a type of pigment in black rice that is classified as a flavonoid compound and has antioxidant property. This study focused on testing anthocyanin content on four local varieties of black rice in Indonesia, namely Toraja (South Sulawesi), Cempo Ireng (Yogyakarta), Wojalaka (East Nusa Tenggara), and Manggarai (East Nusa Tenggara). Analysis of total anthocyanin content was carried out based on the absorbance value of rice flour extract at a wavelength of 535 nm with a spectrophotometer. This study used a randomized block design with varieties as groups and each was carried out in 20 repetitions. The total anthocyanin content was analysed using a UV-Vis spectrophotometer with an absorbance length of 550 nm and 700 nm. The results showed that there were significant differences in the total anthocyanin content of the four varieties of black rice. Sequentially the anthocyanin levels of black rice varieties from highest to lowest were Manggarai with an average anthocyanin content of 1508.89 ppm, Cempo Ireng with an average anthocyanin content of 734.86 ppm, Wojalaka with an average anthocyanin content of 435.38 ppm, and Toraja with an average anthocyanin level of 117.2 ppm.